2-hydroxy arachidonic acid: a new non-steroidal anti-inflammatory drug. - Daniel H Lopez (Public Library of Science (PLoS), 2013)
Background Nonsteroidal anti-inflammatory drugs (NSAIDs) are a family of COX1 and COX2 inhibitors used to reduce the synthesis of pro-inflammatory mediators. In addition, inflammation often leads to a harmful generation of nitric oxide. Efforts are being done in discovering safer NSAIDs molecules capable of inhibiting the synthesis of pro-inflammatory lipid mediators and nitric oxide to reduce the side effects associated with long term therapies. Methodology/principal findings The analogue of arachidonic acid (AA), 2-hydroxy-arachidonic acid (2OAA), was designed to inhibit the activities of COX1 and COX2 and it was predicted to have similar binding energies as AA for the catalytic sites of COX1 and COX2. The interaction of AA and 2OAA with COX1 and COX2 was investigated calculating the free energy of binding and the Fukui function. Toxicity was determined in mouse microglial BV-2 cells. COX1 and COX2 (PGH2 production) activities were measured in vitro. COX1 and COX2 expression in human macrophage-like U937 cells were carried out by Western blot, immunocytochemistry and RT-PCR analysis. NO production (Griess method) and iNOS (Western blot) were determined in mouse microglial BV-2 cells. The comparative efficacy of 2OAA, ibuprofen and cortisone in lowering TNF-α serum levels was determined in C57BL6/J mice challenged with LPS. We show that the presence of the -OH group reduces the likelihood of 2OAA being subjected to H* abstraction in COX, without altering significantly the free energy of binding. The 2OAA inhibited COX1 and COX2 activities and the expression of COX2 in human U937 derived macrophages challenged with LPS. In addition, 2OAA inhibited iNOS expression and the production of NO in BV-2 microglial cells. Finally, oral administration of 2OAA decreased the plasma TNF-α levels in vivo. Conclusion/significance These findings demonstrate the potential of 2OAA as a NSAID.